2023
DOI: 10.1021/acsmacrolett.2c00650
|View full text |Cite
|
Sign up to set email alerts
|

Poly(N-allyl acrylamide) as a Reactive Platform toward Functional Hydrogels

Abstract: The synthesis of poly(N-allyl acrylamide) (PNAllAm) as a platform for the preparation of functional hydrogels is described. The PNAllAm was synthesized via organocatalyzed amidation of poly(methyl acrylate) (PMA) with allylamine and characterized by 1H NMR spectroscopy, size exclusion chromatography (SEC), and turbidimetry, which allowed an estimation of the lower critical solution temperature of ∼26 °C in water. The PNAllAm was then used to make functional hydrogels via photoinitiated thiol–ene chemistry, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 87 publications
1
9
0
Order By: Relevance
“…These observations strongly support the presence of favorable intrachain interactions, hydrogen bonding in this case, affecting the transition states involved in amidation and provide an explanation for previously reported successful uncatalyzed amidations of PMA with ethanolamine [117] . Both reports also provide a basis for the synthesis of poly(acrylamide)s or poly(acrylamide‐ co ‐acrylate) copolymers in a controlled fashion and enable further processing by subsequent reactions, such as thiol‐ene and Alder‐ene reactions [122,146,147] . Finally, the reactivity of PMA towards a series of N ‐substituted diamines has also been explored, with the intention of eliminating polymer chain coupling reactions typically observed for modifications performed with ethylenediamine.…”
Section: Transformations Of Poly(< Meth >Acrylate)ssupporting
confidence: 82%
See 1 more Smart Citation
“…These observations strongly support the presence of favorable intrachain interactions, hydrogen bonding in this case, affecting the transition states involved in amidation and provide an explanation for previously reported successful uncatalyzed amidations of PMA with ethanolamine [117] . Both reports also provide a basis for the synthesis of poly(acrylamide)s or poly(acrylamide‐ co ‐acrylate) copolymers in a controlled fashion and enable further processing by subsequent reactions, such as thiol‐ene and Alder‐ene reactions [122,146,147] . Finally, the reactivity of PMA towards a series of N ‐substituted diamines has also been explored, with the intention of eliminating polymer chain coupling reactions typically observed for modifications performed with ethylenediamine.…”
Section: Transformations Of Poly(< Meth >Acrylate)ssupporting
confidence: 82%
“…[117] Both reports also provide a basis for the synthesis of poly(acrylamide)s or poly(acrylamide-co-acrylate) copolymers in a controlled fashion and enable further processing by subsequent reactions, such as thiol-ene and Alder-ene reactions. [122,146,147] Finally, the reactivity of PMA towards a series of Nsubstituted diamines has also been explored, with the intention of eliminating polymer chain coupling reactions typically observed for modifications performed with ethylenediamine. We have shown that N-ethyl ethylenediamine was able to provide selective amidation with the primary amine in the presence of a N-ethyl substituted secondary amine.…”
Section: Amidation Of Poly(acrylate)smentioning
confidence: 99%
“…As compared to other approaches for efficient synthetic upcycling of low-reactivity polymers that often rely on continuous removal of byproducts to drive the equilibrium, ,, our strategy resembles others that occur through an irreversible mechanism, obviating the need for specialized experimental setups. Indeed, density functional theory calculations on small-molecule substrates revealed that the N–H bond in the secondary amide product undergoes deprotonation by LiHMDS, resulting in a stable amidate lithium complex, a process that helps to thermodynamically drive the overall transformation .…”
Section: Resultsmentioning
confidence: 99%
“…This process resulted in the formation of poly(Nallyl acrylamide), which served as a reactive platform for creating functional hydrogels through light-driven thiolene reactions. 256 TBD-catalyzed postpolymerization modification (PPM) has been applied to other ester-containing polymers, expanding its scope and potential in functionalizing polymers with specific properties. Öztürk and colleagues explored the utility of TBD in PPM for poly(norbornenediester), focusing on both amidation and esterification reactions.…”
Section: Postpolymerization Modifications Of Ester/ Alcohol Side Groupsmentioning
confidence: 99%
“…Notably, the conversion of PMA to poly( N ‐allyl acrylamide) was acquired by heating a mixture of PMA, TBD (10 mol%), and allyl amine (6 equiv) at 80 °C for 3 days. This process resulted in the formation of poly( N ‐allyl acrylamide), which served as a reactive platform for creating functional hydrogels through light‐driven thiol‐ene reactions 256 …”
Section: Postpolymerization Modifications Of Ester/alcohol Side Groupsmentioning
confidence: 99%